Analisis Brand Strategic Pada Iphone - Nini Nurhayani; M.Farhan Fayyadh; Ahmad Vajri Rahman (CV. ITTC INDONESIA, 2026)
In the increasingly competitive smartphone industry, branding is a key factor in determining a company's success in maintaining its market position and consumer loyalty. The iPhone, Apple Inc.'s flagship product, is an example of a global brand that has successfully built a premium image and strong brand equity. This paper aims to analyze the brand strategy applied to the iPhone by reviewing the concept of brand equity, the process of building and managing brand equity, branding strategies, and the iPhone's brand positioning in the global smartphone industry. The writing method used is a literature study with a descriptive-analytical approach based on brand management and marketing theory. The results of the discussion indicate that the iPhone's success is not only determined by technological innovation, but also by a consistent branding strategy, user experience-based differentiation, and the integration of product and service ecosystems. Apple's branded house strategy is able to strengthen the iPhone's brand value as a premium product with a high level of consumer loyalty. With a positioning that emphasizes quality, design, security, and symbolic value, the iPhone has succeeded in creating a sustainable competitive advantage in the global market.